Metabolic perturbations in methicillin-resistant Staphylococcus aureus induced by Psidium guajava ethanolic leaf extract - Manglicmot Yabes, Ailyn; Orejas Ramos, Monica Angelique (Life Sciences, Medicine and Biomedicine, 2023)
Psidium guajava ethanolic leaf extract (PGele) showed good antibacterial activity against Staphylococcus aureus in various in vitro and in vivo studies. It was also reported to be efficacious, safe, and well-tolerated in a phase 1/11a clinical trial of the Psidium guajava ointment among volunteer patients with persistent Staphylococcus aureus nasal colonizers. However, its mechanism of antibacterial action is yet to be elucidated. Changes in bacterial metabolism can contribute to the susceptibility of the organism to antibiotics, thus screening for metabolic perturbations induced by PGele can give insight into its mechanism/s of antibacterial action. Minimum inhibitory concentration (MIC) of PGele against methicillin-resistant Staphylococcus aureus (MRSA) was determined using the agar dilution technique. The sole carbon utilization phenotype microarray was used to describe the metabolic perturbations. Psidium guajava ethanolic leaf extract showed antibacterial activity against MRSA with MIC at 1,250 µg/mL. The phenotypic profile of MRSA showed utilization of 51 carbon sources, however, when MRSA was treated with the plant extract at sub-MIC (625 µg /mL), the utilization of carbon sources belonging to carbohydrate group (51.43%), amino acid group (100%) and the group of esters, carboxylic acids and fatty acids (75%) were inhibited. The sub-MIC of PGele induced metabolic perturbations on carbon sources associated with Embden-Meyerhof-Parnas pathway (EMP), pentose phosphate pathway (PPP), and citric acid cycle (TCA) pathways of MRSA. This current study gave an insight into the mechanism of antibacterial action of the Psidium guajava ethanolic leaf extract, a promising plant-derived antibiotic.